Prevalence and decay of maternal pneumococcal and meningococcal antibodies: A meta-analysis of type-specific decay rates. Issue 43 (13th October 2017) - Voysey, Merryn; Pollard, Andrew J.; Sadarangani, Manish; Fanshawe, Thomas R.
Abstract: Background: At the time of an infant's initial vaccination at age ∼2 to 3 months, some infants already have maternal antibodies against vaccine antigens and these can suppress the immune response to vaccination. Modelling the effects of maternal antibody and the timing of infant doses on the antibody response to vaccination, requires estimates of the rate of maternal antibody decay. Decay rates are not well characterised in the medical literature. We investigated variation in the prevalence of maternal anti-capsular pneumococcal and meningococcal antibodies in infants in 14 countries, and estimated type-specific half-lives. Methods: Individual participant serological data were obtained from clinical trials. Half-lives were estimated from antibody concentrations in infants who did not receive meningococcal or pneumococcal vaccines. Results: The seroprevalence of maternal pneumococcal antibodies was highest for serotypes 14, and 19F (92% and 80% respectively) and lowest for serotypes 4 and 1 (30% and 34% respectively). Half-life estimates ranged from 38.7 days (95% CI 36.6–41.0) for serotype 6B, to 48.3 days (95% CI 46.7–50.2) for serotype 5. The overall half-life was 42.6 days (95% CI 41.5–43.7). Seroprevalence was highest in Mali, Nigeria, India, and the Philippines, (all >65%) and lowest in the Czech Republic and Finland (both <45%). In studies of meningococcal vaccines, seroprevalence was 13% for group C (half-life 39.8 days, 95% CI 33.4–49.4) and 43% for group A (half-life 43.1 days 95% CI 39.8–47.2). Conclusion: Substantial proportions of infants in many countries have antibodies to vaccine serotypes of pneumococcus, however fewer infants have maternally acquired antibodies to groups A and C meningococcus. Passively-acquired antibodies to capsular polysaccharides decay with a half-life of approximately 6 weeks. These estimates are useful for modelling the impact of proposed vaccination programmes, and consideration of schedules with a delayed start.